Wakefield excitation by sequences of relativistic electron bunches in dielectric cavity at detuning bunch repetition frequency and frequency of eigen principal mode - Balakirev, V.A.; Onishchenko, I.N.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2014)
Process of wakefield excitation by short and long sequences of relativistic electron bunches with finite both longitudinal and the transverse sizes is investigated. It is shown that at the presence of detuning between the bunch repetition frequency and the frequency of excited synchronous oscillations the beating of oscillations in time is formed. The first part of the sequence of bunches loses energy on wakefield excitation resulting in wakefield amplitude growth. The second part of the sequence of bunches gains energy resulting in wakefield amplitude decrease. Thus, in the dielectric cavity the regime of relativistic electrons autoacceleration can be realized by introduction of frequency detuning.